Improved Meet-in-the-Middle cryptanalysis of KTANTAN (poster) - Wei, Lei (2012)
This paper presents ongoing work towards extensions of meet-in-the-middle (MITM) attacks on block ciphers. Exploring developments in MITM attacks in hash analysis such as: (i) the splice-and-cut technique; (ii) the indirect-partial-matching technique. Our first contribution is that we show corrections to previous cryptanalysis and point out that the key schedule is more vulnerable to MITM attacks than previously reported. Secondly we further improve the time complexities of previous attacks with (i) and (ii), now the 80-bit secret key of the full rounds KTANTAN-{32,48,64} can be recovered at time complexity of 272.9, 273.8 and 274.4 respectively, each requiring 4 chosen-plaintexts.